Aplicação da tecnologia do vácuo em projeto de engenharia de precisão - Paiva, Jadilson Alves de (2010)
This work presents the state of the in vacuum technology which covers the fundamentals, devices for generating, measuring and major applications in precision engineering. Also, the design and development of vacuum tables applied to machine tool is shown. With regard to fundamentals, it is described the historical background, classical theories and classification of this technology by bands of applications. It is shown most widely used vacuum generators and gauges, showing their construction, operation and applications within various areas. Applications of vacuum technology in precision engineering that span the macro, micro and nano scales are presented, highlighting their importance in each application area. In addition, a methodology to design and development of vacuum tables to fixture workpieces in machine tools, is described and applied. The development of this methodology was motivated due lack of technical and scientific articles that concern the studies on vacuum tables with emphasis on its design parameters. In this work, vacuum tables with hollow, square and hexagonal cores were analyzed by considering two different magnitudes of machining forces. The displacement and stress that each vacuum table configuration is submitted were determined by using numeric simulation based on the finite element method for both machining conditions.